THE EXPERIENCE OF TREGALOZA BASED LUBRICANT USAGE FOR PATIENTS WHO UNDERWENT EXCIMER LASER SURGERY - E. Eskina; V. A. Parshina; M. Stepanova (Oftalʹmologiâ, 2016)
Purpose: to evaluate the tregalose based eye drops effectiveness in patients who underwent PRK or TransPRK surgery. patients and methods: 50 patients with moderate myopia were examined before, 7 days and 1 month after PRK or TransPRK surgery made by SCHWIND Amaris excimer laser by the same surgeon. In addition to conventional diagnostics, Schirmer test and tear break up time were performed as well as ODSI questionare and Oxford index of ocular surface disorders were investigated. Patients were divided in two groups, Study group — “Thealos” group and “Control” group. In both groups patients have started using non preservative eye drops based on tregalosa and hyaluronic acid 4-th day after surgery respectively. results: The tear film breakup time was significantly better in “Thealos” group (7,22±3,61 sec 7 days postop and 9,36±3,68 sec 1 month postop in comparison to «Control” group 5,21±0,25 (р<0,01) sec and 7,21±2,85 sec respectively (р<0,05)) as well as ocular surface index score in “Thealos” group post surgery was less (0,26±0,38 и 0,85±0,31 marks 7 days postop (р<0,05) and 0,09±0,19 and 0,21±0,4 (р<0,05) 1 month postop respectively). There were no other statistically significant differences found in analysed data. Conclusion: Using of “Thealoz” non-preservative eye drops leads to faster recovery after surface excimer laser ablations in terms of dry eye manifestation, those as tearfilm stability and ocular surface index score, measured using “Oxford” scale. Moistening properties of tregaloze solution could be compared with those of hyaluronic acid solution.